Myocardial infarction and ventricular fibrillation due to iatrogenic right coronary artery occlusion following tricuspid valve annuloplasty: a case report. Issue 6 (15th November 2020) - Poon, Shi Sum; George, Joseph; Obaid, Daniel; Kumar, Pankaj
Abstract: Background: Iatrogenic right coronary artery (RCA) injury is a rare complication of tricuspid valve annuloplasty. Given that surgical intervention is increasingly favoured for tricuspid regurgitation, it is of great importance to recognize potential complications following tricuspid valve surgery. Case summary: A 72-year-old man underwent surgical mitral and tricuspid valve repair. The early post-operative course was complicated by recurrent ventricular fibrillation episodes. Due to haemodynamic instability, a re-sternotomy and another cardiopulmonary bypass run were required. The patient subsequently underwent coronary angiography study which confirmed RCA occlusion. The occluded posterior left ventricular (PLV) branch was reopened by balloon angioplasty. However, despite multiple attempts it was not possible to pass a coronary guide wire into the posterior descending artery (PDA). An intravascular ultrasound examination revealed that the ostium of the PDA was compressed by external factors leaving a narrow slit-like appearance with no accessible lumen. Subsequently, a drug-eluting stent was placed into the PLV branch. The PDA was not accessible on repeated re-canalization attempts. The patient later successfully recovered from the right ventricular myocardial infarction. Discussion: Right coronary artery occlusion should be considered as a differential diagnosis for significant rhythm disturbances and haemodynamic instability in the peri- and post-operative period following tricuspid valve annuloplasty. A low threshold for diagnostic angiography is needed to avoid potential delay in life-saving revascularization.